Growth, Employment and Education: An Application of Multicriteria Analysis to Pakistan (The Pakistan Development Review, 1988)
Development planning is a multicriteria problem. Apart from economic goals (like economic growth, income distribution, employment, price stability, balance of payments, etc.) a set of basic human needs (like food, health , housing, clothing, education, etc.) has to be fulfilled within a limited time horizon. Of course, not all targets of economic policy can reach desirable levels within a plan period given scarce resources and trade-offs between goals and basic needs. Priorities have to be formulated and goals and needs have to be weighted against another. Multicriteria analysis can contribute to this weighing process by circumscribing feasible areas and by quantifying above mentioned trade-offs. The purpose of this paper is to present an illustration of multicriteria analysis in which at least two goals of economic policy (growth and employment) and one basic human need (education) are incorporated. The model is applied to Pakistan due to data access.